IMPORTANCE OF THE START-UP OF THE ANGREN-POP ELECTRIFIED RAILWAY - Izatillo Omonov (Innovate Conferences, 2025)
From the first years of Uzbekistan's independence, opening new routes to the world market, construction of new railways, an international transport route connecting Europe with Asia, sustainable development of the Uzbek economy.
Keywords: Modernization, highway